FOSTERING STUDENTS"™ MOTIVATION THROUGH PROBLEM-BASED LEARNING IMPLEMENTATIONS ON ELEMENTS, COMPOUNDS, AND MIXTURES TOPIC/MATERIAL - Aliyatunnisa, Shofiyya; Winarno, Nanang; Fadly, Wirawan; Aritonang, Rika Magdalena (Jurnal Pendidikan Matematika dan IPA, 2025)
Motivation is an important factor influencing student success in science learning. Motivation not only encourages students to get involved and active in the learning process but is also helpful in overcoming various possible challenges faced during activity learning. This research aims to analyze the influence of applying the Problem-Based Learning (PBL) model on students' motivation on elements, compounds, and mixtures. This research uses a pre-experimental design study with one group pretest-post-test. Data collection tools use the Science Motivation Questionnaire. A study was done in one school in Bandung City, Indonesia. The sample used in this research consisted of 24 students at this level, class VIII. Research results show a significant influence on students' motivation, with a pretest average of 3.44 and a post-test average of 3.56. N-Gain score on each factor, intepreted as low. It can be seen that the N-Gain score on the instrinsic motivation and personal relevance factors are 0.02, on self-efficacy and assessment anxiety factors are 0.11, on self-determination factor are 0.13, on career motivation factor are 0.08, and on the grade motivation factor are 0.10. Based on the results of research, it is said that a Problem-Based Learning (PBL) model can increase motivation for students to study natural sciences. However, its effectiveness is low.